2021
DOI: 10.3390/ijerph18084036
|View full text |Cite
|
Sign up to set email alerts
|

Using Pressure-Driven Membrane Processes to Remove Emerging Pollutants from Aqueous Solutions

Abstract: Currently, there is great concern about global water pollution. Wastewater generally contains substances called emerging pollutants, and if the removal of these pollutants is not given sufficient attention, the pollutants can enter into the water cycle and reach the water supply for domestic use, causing adverse effects on the well-being of people. In order to avoid this menace, a multitude of techniques to reduce the high concentration levels of these substances dissolved in water are being researched and dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…It can be observed that the differences obtained are a consequence of the pressure and temperature range used in the tests, as well as the type of flow through the membrane, which can vary depending on the experimental equipment used. The highest permeability coefficients are obtained in tests conducted in other studies at pressures higher than 10 bar [21,23].…”
Section: Initial Membrane Characterisationmentioning
confidence: 69%
See 4 more Smart Citations
“…It can be observed that the differences obtained are a consequence of the pressure and temperature range used in the tests, as well as the type of flow through the membrane, which can vary depending on the experimental equipment used. The highest permeability coefficients are obtained in tests conducted in other studies at pressures higher than 10 bar [21,23].…”
Section: Initial Membrane Characterisationmentioning
confidence: 69%
“…For each compound, four assays are conducted, where, in each one, the feeding concentration is kept constant at 5, 10, 15, and 25 ppm while the pressure varies from 5 to 20 bar. The experimental conditions tested-temperature 20 ± 1 • C; range of pressures; and concentrations-were selected taking into account other previous works [21]. (3) Experimental series for the final membrane characterization: This series includes the same assays as the first experimental series, but they are conducted after the experimentation with the emerging contaminants has been completed.…”
Section: Experimental Seriesmentioning
confidence: 99%
See 3 more Smart Citations